Odpowiedzi

2010-03-29T18:40:57+02:00
A)-3/7-1(jedna cała)11/14+2(dwie całe)3/14=
=-6/14-1(jedna cała)11/14+2(dwie całe)3/14=
-1(jedna cała)17/14+2(dwie całe)3/14=
-2(dwie)3/14+2(dwie całe)3/14=0

b)-1,2:0,3*(-2/5)=-4*(-2/5)=8/5=1(jedna cała)3/5

c)4(cztery całe)2/3-3(trzy całe)1/3*2(dwie całe)1/2=
=4(cztery całe)2/3-10/3*5/2=
=4(cztery całe)2/3-25/3=4(cztery całe)2/3-7(siedem całych)4/3=
=-3(trzy całe)2/3

d)3(trzy całe)3/4*1(jedna cała)1/5+(-1,5):2,4-1/4=
=15/4*6/5-3/2*5/12-1/4=
=9/2-5/8-1/4=36/8-5/8-2/8=36/8-7/8=
=29/8=3(trzy całe)5/8